3x-(-20)=-1

Simple and best practice solution for 3x-(-20)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-(-20)=-1 equation:



3x-(-20)=-1
We move all terms to the left:
3x-(-20)-(-1)=0
We add all the numbers together, and all the variables
3x+21=0
We move all terms containing x to the left, all other terms to the right
3x=-21
x=-21/3
x=-7

See similar equations:

| 8(5y+4)=31 | | 10-3x=15-2x | | y=-2,129.75*1000+21,028.35 | | 36x=112 | | 6x-1=8x5 | | 3x-425=1314 | | 5x•2=2x•15 | | 16=-3f-6f | | -24/2+30/6x=3x-6 | | 7x-9x=9 | | 20x+5=7x+29 | | 9x-6+132=180 | | -14x-19=333 | | 3.15x+9.3=5.5x | | 1805=15(x+19) | | 7x+(-10)=9x+14 | | 720–45x=180 | | x-0.2x=13000 | | x/2+12=6 | | 9=7/10xx | | 25~11/12b=47 | | 2(x-5)+x=3(x-8) | | 9x-6=132 | | 5.00+.65=10+.45x | | n+32=59 | | v/3+6=8 | | -6x-1=-3 | | 10x-75=-12.50-90x= | | -4h+8-6h=27 | | -(q-5)=(8q-4)-4 | | 7(-8n+6=490 | | 17-8k=-8k+16 |

Equations solver categories